OCCUPATIONAL DISEASES ARISING IN THE MEDICAL SECTOR: ANALYTICAL AND STATISTICAL REVIEW OF PROFESSIONAL HEALTH RISKS - Mamadaliyev Avaz Abduraximovich (Bright Mind Publishing, 2025)
Occupational diseases among healthcare workers remain a persistent and globally significant public health challenge, particularly in the context of rapidly evolving medical technologies, increasing patient loads, and prolonged exposure to hazardous occupational factors. Medical professionals working in surgical units, emergency departments, laboratories, intensive care units, and primary healthcare settings are exposed daily to a complex combination of biological, chemical, physical, ergonomic, and psychosocial risks that cumulatively contribute to the development of work-related diseases. This analytical and statistical review aims to systematically examine the spectrum, prevalence, and underlying mechanisms of occupational diseases arising in the medical sector, based on a comprehensive analysis of international and regional scientific literature complemented by hypothetical statistical modeling. The study evaluates the most common categories of occupational diseases, including musculoskeletal disorders, infectious diseases, allergic and respiratory conditions, radiation-induced pathologies, chemical intoxications, and stress-related mental health disorders, emphasizing their etiological factors and risk gradients across different medical specialties. Special attention is given to high-risk professional environments such as operating theaters, clinical laboratories, ambulance services, and emergency care units, where exposure intensity and cumulative risk are significantly elevated. The findings highlight the multifactorial nature of occupational morbidity in healthcare settings and underscore the critical role of organizational, technological, and behavioral determinants in disease formation. The results of this review demonstrate that despite advancements in occupational safety standards, the incidence of professional diseases among healthcare workers remains unacceptably high, largely due to insufficient preventive measures, inconsistent compliance with safety protocols, and chronic workforce overload. The study concludes that strengthening occupational health surveillance systems, implementing targeted preventive strategies, and integrating evidence-based risk management approaches are essential to reducing the burden of occupational diseases in the medical sector.
Keywords: Occupational diseases, healthcare workers, professional health risks, medical personnel, workplace hazards, analytical review.